The Impact of the Regional Financial Management Information System (SIMDA), Human Resource Competency, and Internal Control Systems on the Quality of Financial Reports at the Education and Culture Office of North Labuhanbatu Regency - Silaen, Aprilia Putri; Syafina, Laylan; Ilhamy, M Lathief (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2026)
This study aims to analyze the influence of the Regional Financial Management Information System (SIMDA), Human Resource Competency, and Internal Control Systems on the Quality of Financial Reports at the Education and Culture Office of North Labuhanbatu Regency. This study employs a quantitative approach using a survey method. The results indicate that, individually, the SIMDA does not have a significant effect on the quality of financial reports, whereas human resource competency does have a significant effect on the quality of financial reports. Meanwhile, the internal control system, when considered individually, also does not have a significant effect on the quality of financial reports. However, the results of the simultaneous test indicate that the SIMDA, human resource competency, and the internal control system collectively have a significant effect on the quality of financial reports at the Education and Culture Office of North Labuhanbatu Regency. These findings indicate that the quality of financial reports will be optimal if supported by adequate staff competence as well as integration between the SIMDA and the implementation of the internal control system. Thus, improving the quality of local government financial reports needs to focus on strengthening human resource competence accompanied by the optimized utilization of the SIMDA and the internal control system in an integrated manner.